PERAN MANAJEMEN LEMBAGA PENGEMBANGAN TILAWATIL QUR’AN (LPTQ) DALAM MENINGKATKAN PEMBINAAN KUALITAS PENDIDIKAN AKHLAK MULIA KADER QORI’- QORI’AH - Saraka; Mansyah, Mansyah; Hanim, Zaenab (BEduManagers Journal : Borneo Educational Management and Research Journal, 2021)
Tilawatil Qur’an Development Institution in an organization that carries cut education of the Qur’an together with the islamic community in preparing the generation of the Qur’ani who read the Al-Qur’an with reading that are recognized by the world, as well as having morality the Tilawatil Qur’an development institute began in 1977. Organization of education Al-Qur’an as well as the tilawatil musabaqah the Qur’an is carried out with a patterm of management that acounteble by LPTQ stags starting from the village level, distract level ,District /City level, Provincial level and National level. Specifically LPTQ Samarinda city has tried to empower all potential generations of Muslim to be able to inherit the art of reading the Qur’an propertly, practicing in daily life, especially the people of Samarinda and East Kalimantan in general. So for the Tilawatil Qur’an development instiut of Samarinda city has built patnerships with islamic communiteis MTQ implementation ,guidance of the board of judges and impropvement of the quality of the participans in reading of study Al-Qur’an are the min programs of the LPTQ of Samarinda city.